What is the value of the expression: -1+2*3-1+(3*4)
To solve the above mentioned expression, we need to learn about BODMAS rule which goes as follows: B -> Brackets O -> Orders or Powers D -> Division M -> Multiplication A -> Addition S -> Subtraction Let us look at our expression now: = -1+2*3-1+(3*4) As we can see, there is one bracket in the expression mentioned above, So we will start our solution with 'B' for brackets in BODMAS. The expression reduces to: = -1+2*3-1+12 As there are no powers or division sign in the expression, we directly move to 'M' for Multiplication as follows: = -1+(2*3)-1+12 = -1+6-1+12 Now this tricky! We know that as per BODMAS rule, addition needs to be performed first. But what if we have two additions at two ends of the equation! Simple..Got left to right in that case. Let us see how. Let us put virtual brackets in the equation to make it more clear = (-1+6)-1+12 = 5-1+12 = 5+(-1+12) = 5+11 = 16 So, the answer is 16.
Find the next number in series: 3, 8, 23, 68, __
Let us try to find the common behavior in all the numbers mentioned: 3*3-1 = 8 8*3-1=23 23*3-1=68 Once, we identify the repeated behavior, we can find the next number as: 68*3-1 = 203 Answer: 203
What is the value of x in expression: x^2-1=0?
Let x^2-1=0 is equation 1 Formula in use: a^2-1^2 = (a-1)(a+1) Applying the formula in equation 1, we get, x^2-1^2=0 (x-1)(x+1)=0 This implies, x-1=0 or x+1=0 Hence, value of x= 1 or -1